2002
DOI: 10.1128/mcb.22.13.4943-4951.2002
|View full text |Cite
|
Sign up to set email alerts
|

Maleylacetoacetate Isomerase (MAAI/GSTZ)-Deficient Mice Reveal a Glutathione-Dependent Nonenzymatic Bypass in Tyrosine Catabolism

Abstract: In mammals, the catabolic pathway of phenylalanine and tyrosine is found in liver (hepatocytes) and kidney (proximal tubular cells). There are well-described human diseases associated with deficiencies of all enzymes in this pathway except for maleylacetoacetate isomerase (MAAI), which converts maleylacetoacetate (MAA) to fumarylacetoacetate (FAA). MAAI is also known as glutathione transferase zeta (GSTZ1). Here, we describe the phenotype of mice with a targeted deletion of the MAAI (GSTZ1) gene. MAAI-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 35 publications
8
71
0
Order By: Relevance
“…Decreases in cellular glutathione levels have previously been shown to prevent the execution of programmed cell death, but it has also been reported that glutathione depletion enhances the HGA toxicity in Fah -/-mice. 23 Importantly, glutathione levels were not reduced in HT1 mice 2 weeks off NTBC: levels on NTBC were 5.1 ϩ 1.9 mmol/ g liver protein (n ϭ 4); levels off NTBC were 6.9 ϩ 1.54 mmol/ g liver protein (nϭ4). This indicated that decreases in glutathione levels were not the mechanism for cell death resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Decreases in cellular glutathione levels have previously been shown to prevent the execution of programmed cell death, but it has also been reported that glutathione depletion enhances the HGA toxicity in Fah -/-mice. 23 Importantly, glutathione levels were not reduced in HT1 mice 2 weeks off NTBC: levels on NTBC were 5.1 ϩ 1.9 mmol/ g liver protein (n ϭ 4); levels off NTBC were 6.9 ϩ 1.54 mmol/ g liver protein (nϭ4). This indicated that decreases in glutathione levels were not the mechanism for cell death resistance.…”
Section: Resultsmentioning
confidence: 99%
“…GSTZ1 was independently characterized as maleylacetoacetate isomerase (MAAI) and plays a putative isomerase role in the catabolic pathway of phenylalanine and tyrosine in addition to the GSH-dependent transformation of ahalogenated acids (Fernandez-Canon et al, 2002). GSTZ1 is preferentially expressed in hepatocytes and renal proximal tubule cells where phenylalanine and tyrosine are catabolized.…”
Section: Zeta Classmentioning
confidence: 99%
“…GSTZ1/MAAI converts maleylacetoacetate to fumarylacetoacetate (FAA). GSTZ1-deficient mice have an elevated urinary excretion of FAA and were subject to renal injury following phenylalanine and tyrosine overload (Fernandez-Canon et al, 2002). Four families have been identified that have GSTZ1-deficient members that have died within the first year of life.…”
Section: Zeta Classmentioning
confidence: 99%
“…The failure of RNAi directed against D1053.1 is not unexpected as D1053.1 is predicted to encode the enzyme maleylacetoacetate isomerase, which converts MAA to FAA. This isomerization reaction is able to occur even in the absence of this enzyme (48). Hence, RNAi directed against D1053.1 is likely not to rescue worms treated with K10C2.4 RNAi as FAA can still be formed in the absence of D1053.1, MAA may have toxicity on its own, and the tyrosine metabolites SAA and SA can still be formed from MAA.…”
Section: K10c24 Encodes a Homolog Of Fumarylacetoacetatementioning
confidence: 99%
“…The K10C2.4 Phenotype Is Dependent upon Tyrosine and the Tyrosine Degradation Pathway-Mice and fungi with mutations in downstream enzymes in the tyrosine degradation pathway have been shown to be sensitive to levels of dietary tyrosine (44,48). To test whether the observed phenotype is due to altered tyrosine metabolism, we examined the effects of supplemental tyrosine.…”
Section: K10c24 Encodes a Homolog Of Fumarylacetoacetatementioning
confidence: 99%